Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai pada UPT Losari Dinas Pariwisata Kota Makassar - Sulisetiani Sulisetiani; Agung Widhi Kurniawan; Zainal Ruma (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to find out how work discipline influences employee erformance at UPT Losari, Makassar City Tourism Office. The independent variable in this research is work discipline while the dependent variable is employee performance. The researchers conducted research by distributing questionnaires and documentation to 40 respondents. This research uses a quantitative type of research where the population in this study is 40 people using simple regression analysis using (SPSS) Version 25 and Microsoft Excel. The results of this research show that work discipline is significant on employee performance and the results of hypothesis testing with the help of the SPSS version 25 application by carrying out the T test.